2023
DOI: 10.3390/insects14030263
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Potato Psyllid Bactericera cockerelli (Hemiptera: Triozidae) in Australia: Incursion, Potential Impact and Opportunities for Biological Control

Abstract: Incursion and establishment of an exotic pest may threaten natural habitats and disrupt ecosystems. On the other hand, resident natural enemies may play an important role in invasive pest control. Bactericera cockerelli, commonly known as the tomato-potato psyllid, is an exotic pest, first detected on mainland Australia in Perth, Western Australia, in early 2017. B. cockerelli causes direct damage to crops by feeding and indirectly by acting as the vector of the pathogen that causes zebra chip disease in potat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 138 publications
0
4
0
Order By: Relevance
“…Also olinscide Alacris-11 could be used against tomato potato psyllid Bactericera cockerelli Šulc (family Triozidae) (GenBank sequence ID: MT027594.1; range: 734 to 724). B. cockerelli is an important insect pest of potato, tomato, and other solanaceous crops (Sarkar et al 2023). Olinscide Laura-11 could be used against Trioza remota , Foerster (family Triozidae) (GenBank sequence ID: MT038993.1; range: 321 to 311).…”
Section: Discussionmentioning
confidence: 99%
“…Also olinscide Alacris-11 could be used against tomato potato psyllid Bactericera cockerelli Šulc (family Triozidae) (GenBank sequence ID: MT027594.1; range: 734 to 724). B. cockerelli is an important insect pest of potato, tomato, and other solanaceous crops (Sarkar et al 2023). Olinscide Laura-11 could be used against Trioza remota , Foerster (family Triozidae) (GenBank sequence ID: MT038993.1; range: 321 to 311).…”
Section: Discussionmentioning
confidence: 99%
“…Mallada signatus , an aggressive generalist predator thriving in Australian agro‐ecological systems, has been documented preying on various insect pests, including different aphid species (Bahar et al., 2013; New, 2002; Ward et al., 2024). Following a 2‐year field survey across diverse Solanaceous crops, it was found that the green lacewing ( M. signatus ) exhibited the highest abundance (Sarkar, 2023). Moreover, molecular analysis confirmed the predation of B. cockerelli by M. signatus , with 30% of sampled larvae testing positive for B. cockerelli DNA under natural field conditions (Sarkar, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Following a 2‐year field survey across diverse Solanaceous crops, it was found that the green lacewing ( M. signatus ) exhibited the highest abundance (Sarkar, 2023). Moreover, molecular analysis confirmed the predation of B. cockerelli by M. signatus , with 30% of sampled larvae testing positive for B. cockerelli DNA under natural field conditions (Sarkar, 2023). Our current findings demonstrate that B. cockerelli can also serve as a suitable prey, supporting the development and reproduction of M. signatus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation